Advanced PID Controller Synthesis using Multiscale Control Scheme - Ugon, B.; Nandong, Jobrun; Zang, Zhuquan (ICIEA 2014 Organizers, 2014)
For many decades, PID controller has been widely applied in industries despite the advancement in many advanced control techniques. Process models such as the First-Order plus Deadtime (FOPDT) has often been used to design or tune PID controller. Numerous PID tuning formulas have been established since the well-known Ziegler-Nichols formula introduced in the 1940s. In this paper, we present the multi-scale control approach to constructing a PID tuning formula based on the FOPDT model. The effectiveness of the proposed PID tuning formula is compared with some of the existing formulas reported in the literature.